2017
DOI: 10.1515/jpm-2016-0231
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the cervical os in patients after fertility preserving treatment for early cervical cancer – results of a prospective observational study

Abstract: We developed a protocol to reduce the risk of preterm deliveries after a RVT. Digital examinations should be avoided. Vaginal checks for pH can discover ascending infections - the main cause of preterm deliveries after a RVT. Infections should be treated adequately. CCO can further reduce the risk of preterm deliveries after a RVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…When transabdominal cerclage was difficult due to intra-abdominal adhesions, Sneider et al reported that vaginal occlusion in addition to cerclage was useful in preventing recurrent second-trimester miscarriages [39]. Moreover, although there was no statistically significant difference, the closure of the cervical os may be useful to prevent preterm delivery in pregnant women after vaginal RT [40]. [41].…”
Section: Prevention Of Preterm Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…When transabdominal cerclage was difficult due to intra-abdominal adhesions, Sneider et al reported that vaginal occlusion in addition to cerclage was useful in preventing recurrent second-trimester miscarriages [39]. Moreover, although there was no statistically significant difference, the closure of the cervical os may be useful to prevent preterm delivery in pregnant women after vaginal RT [40]. [41].…”
Section: Prevention Of Preterm Deliverymentioning
confidence: 99%
“…Among the pregnant women after RT, there are reports of ten women pregnant with twins published previously (Table 1) [10,40,50,[57][58][59][60][61][62]. Since perinatal outcomes were not reported in detail, there was a dearth of information on managing a twin pregnancy in women after RT.…”
Section: Twin Pregnancymentioning
confidence: 99%
“…Zur Vermeidung von "sehr frühen Frühgeburten"deren Anteil beträgt nach VRT/ART bis zu 50 %sollte ein frühzeitiger Muttermundverschluss erfolgen [79]. Andererseits findet sich nach Trachelektomie auch ein hoher Anteil infertiler Frauen aufgrund von Zervikalstenosen (> 15 %) [80].…”
Section: Zervixkarzinomunclassified
“…Early closure of the cervical os is recommended to prevent very early premature births, which have a reported incidence of up to 50 % after RVT/RAT [79]. However, a high percentage of infertile women (> 15 %) has been reported because of cervical stenosis following trachelectomy [80].…”
Section: Cervical Cancermentioning
confidence: 99%